PENGARUH KEPERCAYAAN, KETERSEDIAAN PRODUK, DAN WORD OF MOUTH TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA TOKO SUSI DI DESA BALUNG SITUBONDO - Miftah Farhan Ramadani; Mohammad Yahya Arief; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
Grocery and wholesale stores are important elements in driving the local economy that not only maintain the availability of basic necessities at affordable prices. The purpose of this study is to analyze and test the influence of Trust, Product Availability, and Word of Mouth on Consumer Satisfaction Through Purchasing Decisions as Intervening Variables at Susi Shop in Balung Village, Situbondo. The sampling technique used Non-Probability Sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Trust has a significant positive effect on Purchasing Decisions, Product Availability has a significant positive effect on Purchasing Decisions, Word of Mouth has a significant positive effect on Consumer Satisfaction, Trust has a significant positive effect on Consumer Satisfaction, Product Availability has a significant effect on Consumer Satisfaction, Word of Mouth has a positive but not significant effect on Consumer Satisfaction, The results of the indirect influence hypothesis test show that the Trust variable on Consumer Satisfaction through Purchasing Decisions has a positive but not significant effect, Product Availability on Consumer Satisfaction through Purchasing Decisions has a positive but not significant effect, Word of Mouth on Consumer Satisfaction through Purchasing Decisions has a positive but not significant effect.